Wastewaters by Electrochemical Advanced Oxidation Processes Using a BDD Anode and Electrogenerated H2O2 with Fe(II) and UVA Light as Catalysts - Brillas,E. (2008)
This paper reports the mineralization of an aromatic pharmaceutical as clofibric acid and the dye indigo carmine in 0.05 M Na2SO4 of pH 3.0 by electrochemical advanced oxidation processes such as anodic oxidation without and with electrogenerated H2O2, electro-Fenton and photoelectro-Fenton using a boron-doped diamond (BDD) anode. These procedures produce the strong oxidant hydroxyl radical in the form of BDD(·OH) from water oxidation at BDD and/or ·OH from Fentons reaction between added Fe2+ and H2O2 generated at the cathode by two-electron O2 reduction. Comparative degradation of both compounds is performed with an undivided electrolytic cell of 100 mL with an O2-diffusion cathode. The effect of current density and pollutant concentration on the degradation rate and current efficiency of the different methods is discussed. The decay kinetics of clofibric acid and indigo carmine and the evolution of their aromatic by-products and final carboxylic acids like oxalic and/or oxamic are described to clarify their reaction sequences. Anodic oxidation is able to completely mineralize both compounds mainly with BDD(·OH). Aromatic pollutants are more rapidly destroyed in electro-Fenton due to their faster reaction with ·OH, but final Fe(III)-oxalate and Fe(III)-oxamate can only be oxidized with BDD(·OH). The most efficient method is photoelectro-Fenton due to the parallel photolysis of Fe(III)-oxalate complexes with UVA light, although Fe(III)-oxamate complexes are not photodecomposed. Under these conditions, the degradation rate can be enhanced using Cu2+ as co-catalyst because Cu(II)-oxalate and Cu(II)-oxamate complexes are quickly destroyed by ·OH. Results on the fast mineralization of 2.5 L of cresols solutions of pH 3.0 by solar photoelectro-Fenton using a flow plant coupled to a solar photoreactor are also reported. The high efficiency and very low operational cost found for this procedure make it useful for the treatment of industrial wastewaters